Sequências descritivas e produção de sentido: uma análise de blogs de adolescentes - Costa, Sílvia Scola da (2012)
In this research, we aimed to analyze descriptive sequences in blogs and the resources that contribute to the cohesion and coherence of these productions. Having theoretical foundation as texts to be studied in interactional and social cognitive perspective. For that specific analysis, a corpus was composed with nine teenagers blogs selected among those available on the internet which the access does not require password, and besides that, it is presented on its composition the author s blog presentation text. The analysis results indicate that the author s blogs in his pontaneous writing on the internet, compose the profile or presentation text with descriptive sequences which reveal referential cohesion of the elements and the sequential cohesion that contribute to the textual coherence. Overall, this study provides reflection on the spontaneous writing of teenagers in the network and how these productions can become significant objects of study in the teaching of the Portuguese language